Analisis Penerimaan Pengguna Aplikasi Go Pendamping Menggunakan Technology Acceptance Model (TAM): Studi kasus Balai Perhutanan Sosial Palembang - Muhammad Arief Pratama; Mulyati Mulyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the level of acceptance and effectiveness of the Go Pendamping application used by field facilitators at the Social Forestry Center of Palembang. The research adopts a quantitative approach using a survey method and is based on the Technology Acceptance Model (TAM) with the addition of the User Satisfaction variable. The variables examined include Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention to Use, and User Satisfaction. Data were collected through questionnaires distributed to active field facilitators selected using purposive sampling, supported by interviews and literature review. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the outer model analysis indicate that all indicators meet the criteria of convergent validity, discriminant validity, and reliability. Furthermore, the inner model analysis shows that Perceived Ease of Use and Perceived Usefulness have a significant influence on user attitudes and behavioral intentions. Behavioral Intention also demonstrates a strong effect on User Satisfaction. The findings conclude that the Go Pendamping application is well accepted by users and effectively supports reporting, monitoring, and evaluation activities in social forestry assistance. This study provides empirical evidence and recommendations for improving the implementation of information systems in public sector organizations.